(untitled) (TAMADDUN NURI JURNALI, 2024)
This article is about the lack of willpower of students, the fact that a person faces internal and external obstacles in the process of voluntary action, and that internal obstacles are characteristic of the person himself and his internal inclinations. The ability of a person to overcome his inner inclinations, control himself and rule over himself is called inner will. External obstacles are found in the surrounding reality. A person’s ability to overcome such external obstacles is called external will. Overcoming external obstacles (external will) and overcoming internal obstacles (internal will) are considered in volitional activity.